Contribution to Accident Prediction Models Development for Rural Two-Lane Roads in Serbia - Draženko Glavić; Miloš Mladenović; Aleksandar Stevanovic; Vladan Tubić; Marina Milenković; Marijo Vidas (Promet - Traffic&Transportation, 2016)
Over the last three decades numerous research efforts have been conducted worldwide to determine the relationship between traffic accidents and traffic and road characteristics. So far, the mentioned studies have not been carried out in Serbia and in the region. This paper represents one of the first attempts to develop accident prediction models in Serbia. The paper provides a comprehensive literature review, describes procedures for collection and analysis of the traffic accident data, as well as the methodology used to develop the accident prediction models. The paper presents models obtained by both univariate and multivariate regression analyses. The obtained results are compared to the results of other studies and comparisons are discussed. Finally, the paper presents conclusions and important points for future research. The results of this research can find theoretical as well as practical application.